Septic arthritis and hemarthroses caused by Haemophilus influenzae serotype A in children - Ravi S. Samraj; Jaime Fergie (MDPI AG, 2016)
Invasive disease caused by Haemophilus influenzae serotype A (Hia) is rare in children. Clinical syndromes caused by Hia include meningitis, sepsis and respiratory tract infections. Septic arthritis is rare in children with invasive Hia infection and hemarthrosis has not been described in the published literature. We report a case of septic arthritis and hemarthrosis caused by Hia infection in a 2.5 year-old-boy and review invasive Hia infection in children.